Contactless Hand Sanitizer for Healthy Village in Corona Pandemic Outbreaks - Hari Maghfiroh; Augustinus Sujono; Henry Probo Santoso; Joko Slamet Saputro (Universitas Sebelas Maret (UNS), 2020)
The corona pandemic has caused global problems, including Indonesia. One way to reduce the spread of the coronavirus is to wash your hands frequently with soap or hand sanitizer. Many types of hand sanitizers were developed to support efforts to prevent the spread of the corona. For this reason, this paper proposes two types of Contactless Hans Sanitizer (CHS) prototypes. Function tests and user satisfaction tests were carried out to determine the performance of the CHS. The test results show that type A CHS which only works fully electrically is more reliable than type B which works with electrical and mechanical systems. Of the 10 respondents, 90% chose CHS type A.